Etching behavior of ZnO:Ga thin films - Duygulu, Nilufer Evcimen; Mustafaoglu, Ummu; Kodolbas, Alp Osman; Karaaslan, Ahmet (CARL HANSER VERLAG, 2018)
Gallium doped zinc oxide (ZnO:Ga) thin films were deposited on glass substrates by means of r.f magnetron sputtering at room temperature, non-reactively. Both the wet chemical etching behavior and the influence of etching time variations on ZnO:Ga films were investigated. 0.1 % HC1 was used as an etchant and the etching time varied in small increments. The thickness of the etched films was determined using scanning electron microscopy (SEM). The etching depth of the ZnO:Ga thin films increased from 13 to 58 % and the resistivity was 10(-3) Omega x cm at different etching times. X-ray diffraction (XRD) results revealed that etching did not influence the crystal structure in a clear way. The (002) peak intensity to thickness ratio reached its maximum at 15 s while full width at half maximum (FWHM) was determined as the minimum. Morphological investigations were conducted using both high resolution scanning electron microscopy (HRSEM) and atomic force microscopy (AFM). The surface of the etched films became rougher and the root mean square (RMS) values increased according to etching time; at 15 s etching the RMS value was calculated to be 8.48 nm. The optical transmittance was measured using an ultraviolet-visible (UV-VIS) spectrophotometer and decreased from 86.60 to 82.50% while haze increased from 0.85 to 16.68%.
Keywords: Ga doped ZnO; transparent conductive oxide; wet chemical etching; high resolution scanning electron microscopy; atomic force microscopy; ZINC-OXIDE-FILMS; SUBSTRATE-TEMPERATURE; OPTICAL-PROPERTIES; SOLAR-CELLS; AZO; Materials Science